ESTROUS AND FERTILITY RESPONSE IN ESTROUS SYNCHRONIZED LWY CROSSBRED PREPUBERTAL GILTS - Rao, K Prabhakar; BRAMHAIAH K, VEERA; NAIDU, G VENKATA; KUMAR, R V Suresh; Prameela, D RANI; BABU, D SURESH (The Indian Journal of Animal Reproduction, 2023)
This study was undertaken to assess estrus and fertility response in LWY Gilts synchronized with Prostaglandin5 mg, Prostaglandin 7.5 mg, PMSG 400 IU+HCG 200 IU and 5 ml of Normal Saline in LWY crossbred gilts duringsummer and winter seasons. The mean estrus during winter and summer seasons was 100, 83.33, 83.33 and 66.67percent and 66.67, 66.67, 66.67 and 50.00 percent, respectively. The difference in the interval between treatmentand onset of estrus and the intensity of estrus between seasons and between protocols in each season were significant(P
Keywords: Synchronization of estrus; Estrus response; Season; LWY; Gilts